REFLEXOLOGY AS A COMPLEMENTARY THERAPY FOR REDUCING NAUSEA AND VOMITING IN PEDIATRIC DIARRHEA : LITERATURE REVIEW - Zulva, Siti; Regidor III Dioso; Mohamed Saifulaman Mohamed Said (Journal of Nursing Culture and Technology, 2025)
Background: Diarrhea in children remains a significant global health concern, often accompanied by nausea and vomiting, leading to dehydration and hindered recovery. While oral rehydration solutions and pharmacological therapies are common treatments, the limitations and side effects of the latter have prompted interest in non-pharmacological interventions, such as reflexology. Objective: This literature review aims to explore current evidence regarding reflexology as a complementary therapy for reducing nausea and vomiting symptoms specifically in pediatric patients with diarrhea. Method: A literature review was conducted, analyzing selected articles from databases including Scopus, ProQuest, Clinical Key Nursing, and Sage, covering the years 2020-2025. Keywords used included "reflexology in children," "diarrhea," and "complementary therapy." The selection process involved excluding articles based on publication year, language, duplication, and absence of a comparison group, resulting in a final set of four articles. Results: Four articles were included in the review. Reflexology demonstrates potential for reducing nausea and vomiting, alongside improving comfort and well-being in pediatric patients experiencing diarrhea. This highlights reflexology as a viable option for providing a safe, non-pharmacological approach to managing gastrointestinal symptoms. Conclusion: Reflexology shows promise as a valuable complementary therapy for alleviating nausea and vomiting in children with diarrhea. Integrating reflexology into pediatric care offers a holistic approach that prioritizes patient comfort and enhances treatment outcomes. Future research should focus on rigorous methodologies and larger-scale studies to validate its effectiveness and support its integration into clinical practice.